2023
DOI: 10.3390/ijms24010806
|View full text |Cite
|
Sign up to set email alerts
|

RPS24 Is Associated with a Poor Prognosis and Immune Infiltration in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the most common type of primary liver malignancy, with increased mortality and morbidity. Accumulating evidence suggested that 40S ribosomal protein S24 (RPS24) is related to malignant outcomes and progression. However, the role of RPS24 remains unclear in HCC. The mRNA and protein expression pattern of RPS24 in HCC was explored and confirmed based on the bioinformatics analysis and histological examination. The correlation between RPS24 expression and clinicopathological feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“… 43 Notably, some ribosomal proteins are involved in regulating immune infiltration in the TME. 20 , 44 However, the effect of RPL22L1 in the immune infiltration of LUAD is not fully clear. Our study was the first to reveal that RPL22L1 expression was negatively correlated with the majority of immune cell infiltration, including NK cells, DC cells, B cells, macrophages, CD4+ T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 Notably, some ribosomal proteins are involved in regulating immune infiltration in the TME. 20 , 44 However, the effect of RPL22L1 in the immune infiltration of LUAD is not fully clear. Our study was the first to reveal that RPL22L1 expression was negatively correlated with the majority of immune cell infiltration, including NK cells, DC cells, B cells, macrophages, CD4+ T cells.…”
Section: Discussionmentioning
confidence: 99%
“… 18 It has been found that RPs are involved in regulating immune cell infiltration in the TME. 19 , 20 Futhermore, a study has demonstrated that RPL22L1 affects the development of lymphocytes. 21 Therefore, it is worth investigating whether RPL22L1 is involved in the regulation of the TME, which in turn influences LUAD progression.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative splicing has been proposed as the 11th hallmark of cancer [17], and we showed that RPS24L levels correlate with hypoxia in human prostate tumor samples [14]. Without reference to splicing isoforms or hypoxia, other groups have found that global RPS24 levels are high in prostate [18] and hepatocellular cancer [19], and show that RPS24 is an oncoprotein [20]. Therefore, we set out to investigate the stimuli and mechanisms that contribute to the increase of RPS24L relative abundance compared to RPS24S and the biological impact this has on hypoxic cells.…”
mentioning
confidence: 89%
“…Prediction of the functional effects of these fusion genes is challenging, but individual components, like the ribosomal protein 24 (RPS24) can act as oncoproteins, e.g. in different colon and prostate cancer cell lines (Kazerounian et al, 2016;Li et al, 2023;Wang et al, 2015).…”
Section: Nanopore Sequencing Enables Simplification and Putative Reco...mentioning
confidence: 99%